196 institutions in Honduras, Colombia, Guatemala and Nicaragua have adopted Local-Technical Agroclimatic-Committees (LTACs) approach as a mechanism to reduce agroclimatic-risks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
Regional south-south exchanges and continuous engagement for scaling-out the CCAFS-LTAC approach with institutions in Honduras(90), Colombia(80), Guatemala(18), and Nicaragua(8) have led to the creation of 13 new LTACs and strengthening of 5 existing LTACs across the four countries. The initiative has enabled the empowerment of more than 190 institutions including farmer-organizations, private-sector, international-NGOs, and governmental-organizations, through new capacities related to participatory generation, provision, interpretation and use of forecast-based recommendations for adaptation to climate variability led by CIAT’s modelling-team.